Learning Strategies for High School Students: Differences in Learning Outcomes Problem Based and Expository - Situmorang, Harningsih Fitri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper aims to determine the economics learning outcomes of students who are taught with problem-based learning strategies with expository-based economics learning strategies for students. The problem of this paper lies in the strategy or process of the results of problem-based student learning activities with expository. The data in this study used a population of 116 students who became respondents. Research Quasi-experimental method with a comparative study approach with a 2x2 factorial design descriptive statistical test and continued to inferential statistics using two-way ANOVA with a significant level of signifikan=0.05. the results of the scheffe test (comparative study), followed by the scheffe test (comparative study) and the findings in the field that the economics learning outcomes of students taught with problem-based learning strategies were higher than the economics learning outcomes of students taught with expository learning strategies with a value of f-count = 4,879 >Ftable=3.99 at the significant level =0.05.